Curricular integration of the SDGs and the Sustainability in Corporate Finance - Grau Grau, Alfredo; Bel Oms, Inmaculada; Rodrigo González, Amalia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In 2015, the UN approved 17 Sustainable Development Goals (SDGs) integrated into the 2030 Agenda. Following this line, and given its relevance, European universities are integrating sustainable development into their syllabus. The objective of this proposal will be to develop a pilot experience where our students, through cooperative learning, forming work teams grouped according to the Riso-Hudson test (1999), guarantee maximum academic performance. As a result, a measure of the profitability provided by the incorporation of sustainability in business investment projects along with the creation of sustainable value will be offered.